2011
DOI: 10.1038/nchembio.694
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying polyglutamine protein species in situ that best predict neurodegeneration

Abstract: SUMMARY Polyglutamine (polyQ) stretches exceeding a threshold length confer a toxic function on proteins that contain them and cause at least nine neurological disorders. The basis for this toxicity threshold is unclear. Although polyQ expansions render proteins prone to aggregate into inclusion bodies (IBs), IB formation may be a neuronal coping response to more toxic forms of polyQ. The exact structure of these more toxic forms is unknown. Here we show that monoclonal antibody (mAb) 3B5H10 recognizes a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
179
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(192 citation statements)
references
References 51 publications
12
179
0
1
Order By: Relevance
“…Some have suggested that the inclusion bodies themselves containing aggregated protein fragments are not so pernicious (45). Instead, the toxicity of small oligomeric species of mutant protein fragments that have adopted specific conformational states may be critical (46,47). Arrasate et al (48) have shown that, rather than the total HTT level determining cell death, the amount of diffuse intracellular HTT predicts whether cell death occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that the inclusion bodies themselves containing aggregated protein fragments are not so pernicious (45). Instead, the toxicity of small oligomeric species of mutant protein fragments that have adopted specific conformational states may be critical (46,47). Arrasate et al (48) have shown that, rather than the total HTT level determining cell death, the amount of diffuse intracellular HTT predicts whether cell death occurs.…”
Section: Discussionmentioning
confidence: 99%
“…For polyQ-containing proteins, oligomers form before IBs, their formation is polyQ length-dependent, and their presence is well correlated with cell death (25,37). Both chaperones that remodel oligomers and peptides that inhibit oligomer formation suppress toxicity (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…To detect soluble HTTex1Q49 molecules we used the monoclonal antibody 3B5H10, which exclusively recognizes expanded polyQ tracts in soluble HTT molecules (Miller et al 2011). An analysis of time-resolved HTTex1Q49 aggregation assays with dot-blot assays revealed that soluble 3B5H10-reactive HTT molecules disappeared at a slower rate in the presence of wild-type CRMP1 than in the presence of mutant CRMP1-D408V (Fig.…”
Section: Crmp1 Directly Targets Mutant Htt Fragments and Reduces Theimentioning
confidence: 99%
“…Alternatively, evidence has been provided that the toxic species in HD may be diffusible oligomeric or protofibrillar HTT aggregates with pathogenic polyQ tracts (Hands and Wyttenbach 2010). In contrast to large inclusion bodies, these smaller structures are described as highly mobile and able to associate with numerous cellular proteins, leading to abnormal protein-protein interactions and dysfunction of a range of important cellular processes (Miller et al 2011).…”
mentioning
confidence: 99%